In vitro cleavage and development of buffalo oocytes with semen from different bulls - YADAV, P S; HOODA, O K; SAINI, ANIL; JINDAL, S K (The Indian Journal of Animal Sciences, 2014)
The present study was aimed to compare the cleavage and development rate of buffalo oocytes inseminated with semen from different bulls. Cleavage rate of zygotes reflects the potential of fertilized oocytes to divide to more than 2 cell stage. In this study frozen semen of 4 Murrah buffalo bulls was used for insemination of in vitro matured oocytes. The number of in vitro matured oocytes inseminated from 4 bulls was 122, 85, 61 and 111 respectively. The cleavage rates were 70.4, 42.4, 91.8 and 72.9%, respectively, and were significantly lower in group 2. Bulls did not affect further development of embryos to morula and blastocysts stages. The results suggested that variation was at fertilization level and once cleavage started there was no variation due to bull on further development of embryos.